2002
DOI: 10.1164/rccm.200202-088oc
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation–induced Diaphragmatic Atrophy Is Associated with Oxidative Injury and Increased Proteolytic Activity

Abstract: Prolonged mechanical ventilation (MV) results in reduced diaphrag-matic maximal force production and diaphragmatic atrophy. To investigate the mechanisms responsible for MV-induced diaphrag-matic atrophy, we tested the hypothesis that controlled MV results in oxidation of diaphragmatic proteins and increased diaphrag-matic proteolysis due to elevated protease activity. Further, we postulated that MV would result in atrophy of all diaphragmatic muscle fiber types. Mechanically ventilated animals were anesthe-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
345
3
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(399 citation statements)
references
References 35 publications
41
345
3
10
Order By: Relevance
“…Heart rate (365 Ϯ 9 beats/min) and mean blood pressure (90 Ϯ 4 mm Hg) homeostasis were maintained during MV across all treatment groups. Blood gas homeostasis and pH (data not shown) were maintained within physiologic levels during the experiment as reported previously (1,4,6,18). Because sepsis is associated with diaphragmatic contractile dysfunction, strict aseptic techniques were followed throughout the experiments (1,4,6,18).…”
Section: H Of MVmentioning
confidence: 79%
See 2 more Smart Citations
“…Heart rate (365 Ϯ 9 beats/min) and mean blood pressure (90 Ϯ 4 mm Hg) homeostasis were maintained during MV across all treatment groups. Blood gas homeostasis and pH (data not shown) were maintained within physiologic levels during the experiment as reported previously (1,4,6,18). Because sepsis is associated with diaphragmatic contractile dysfunction, strict aseptic techniques were followed throughout the experiments (1,4,6,18).…”
Section: H Of MVmentioning
confidence: 79%
“…This notion is supported by the observations that new nuclei are incorporated into locomotor skeletal muscle fibers during growth and that nuclei are lost during atrophy (12,14,16). Although it is known that controlled MV decreases protein synthesis and induces proteolysis and myofiber atrophy across all fiber types (6,17,18), it is unknown whether the myonuclear domain of diaphragm myofibers is altered during the fiber atrophy associated with MV.Regulation of myonuclear loss in skeletal muscle could occur through extrinsic death receptor and intrinsic (sarcoplasmic reticulum and mitochondrial) mediated pathways (19). Caspase (cysteine-dependent, aspartate-directed protease) activation results in protein cleavage and functions in intrinsic and extrinsic pathways of apoptosis.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Animal studies have clearly demonstrated that CMV impacts the diaphragm by promoting contractile dysfunction, increased proteolysis and atrophy [17,36]. Interestingly, our results reveal that administration of a relatively low dose of methylprednisolone (5 mg/kg, corresponding ~0.8 mg/kg in humans [19]) exacerbates the CMV-induced diaphragm dysfunction, whereas a higher dose (30 mg/kg, corresponding ~5 mg/kg in humans [19]) completely protected the diaphragm against VIDD.…”
Section: Discussionmentioning
confidence: 99%
“…This study and a previous CMV study, in which we used a calpain inhibitor [9], confirm the important role of the calpain system in the development of VIDD. It is known that three major proteolytic systems are upregulated in the diaphragm during mechanical ventilation: the ubiquitin proteasome system (UPP), the Ca 2+ -dependent calpain system and the lysosomal system [15-17]. Although the UPP is considered a major proteolytic system in skeletal muscle, it cannot degrade intact myofilaments.…”
Section: Introductionmentioning
confidence: 99%